Determinants of Chronic Energy Deficiency (CED) in Pregnant Women in the Lere Health Center Working Area, Palu City in 2021-2023 - Widyayanti, Asri; Sarliana; Dewie, Artika; Silfia, Niluh Nita (EMBRIO: Jurnal Kebidanan, 2025)
Chronic energy deficiency (CED) in pregnant women has an impact on the fetus in the womb. Data on pregnant women with KEK cases in Palu City ranks third with 985 (12.74percent). Lere Health Center is ranked eighth, with the number of CED pregnant women of 64 people (10.47percent) in 2022 and 48 people (39.3percent) in 2023. This research aims to determine the Determining Factors of Chronic Energy Deficiency (CED) in Pregnant Women in the Lere Community Health Center Working Area, Palu City. 2021-2023. The research method used a case-control design with a retrospective approach and was carried out at the Lere Community Health Center, Palu City. The population of all pregnant women in 2021-2023 is 314 people.  The sample was 172, divided into 86 cases (CED) and 86 controls (not CED). The sampling technique uses purposive sampling. The research uses secondary data from medical record books: univariate and bivariate data analysis using the chi-square test. Based on bivariate analysis, the study results showed that maternal age and education factors were unrelated to the incidence of CED in pregnant women, with a p-value of 0.197 and 0.130, respectively. In contrast, the factors of parity and maternal HEG condition were related to the incidence of CED with p-values ​​of 0.004 and, respectively. 0.001. The conclusion is that the determinants of chronic energy deficiency in pregnant women in the Lere Community Health Center work area are the Parity factor and HEG Condition. It is recommended that the Community Health Center provide education regarding the factors that can cause CED in pregnant women.